Corporate Governance Factors On Audit Report Lag - Destin Alfianika Maharani; Paulina Rosna Dewi Redjo (LPPM ISNJ Bengkalis, 2023)
This research aims to determine the effect of committee size, committee meetings, audits, the proportion of independent commissioners, the board size, and company size on audit report lag. The research population is companies that are members of the Jakarta Islamic Index for 2017-2019. Determination of the sample using purposive sampling technique, with predetermined criteria, to obtain 45 samples. This research is quantitative research whose data sources use secondary data originating from documentation in the form of company annual reports and literature. The analysis technique in this research uses a multiple linear regression approach. The research results show that audit committees and company size do not affect audit report lag. Audit committee meetings, the proportion of independent commissioners, and the size of the board of directors partially have a positive and significant effect on audit report lag. Audit committee size, audit committee meetings, the proportion of independent commissioners, board of directors size, and company size significantly affect audit report lag. This theory research can complement existing research results; then, it can be used as a reference for auditors in managing the period in conducting audits.